Dark energy in string cosmology - Sousa, Gabriel Lucas Andrade de (2021)
In this master thesis, three string-inspired cosmological models are compared: string (brane) gas, holographic, and chameleon cosmologies. More precisely, dark energy features are found and the cosmological constant problem is analyzed in each scenario. Their possible solutions to this problem are quite different and common ground is hard to be found. While, within string gas cosmology, dark energy traits only appear in the primordial Hagedorn phase (analogous to inflation in standard cosmology) and have hardly anything to do with the currently observed cosmological constant, both holographic and chameleon cosmologies give us interesting insights on the dominant energy density in the universe today. On one hand, within holographic cosmology, one can map the cosmological constant problem to a renormalization group (RG) flow in the dual field theory. Then, the problem can be “holographically solved”, even though the precise mechanism for the bulk solution is unknown. On the other hand, the chameleon setup encourages us to motivate a scalar potential for a modulus to create a quintessence model, hoping to explain the currently observed dark energy density. In the end, it is attempted to implement the chameleon idea in the original Kaluza-Klein theory, proposing a quintessence model from its scalar field. After fixing some problems with the initial idea, it is found that the scalar potential is still not suitable to have had relevant implications on structure formation in the universe.